Organizational Capital of the Enterprise - Belkin, Vladimir Nikiforovich; Belkina, Nadezhda Andreyevna; Antonova, Olga Anatolyevna (Economy of Regions, 2016)
In the article, the main theoretical questions of the organizational capital of the enterprise are considered. The concept of «organizational capital of the enterprise» as a system consisting of three subsystems (organization of production, labor organization and management) is introduced. It is shown that the organizational capital forms the labor relations system at the enterprise consisting of the cooperation, technological, economic, moral labor relations and the relations of workers’ responsibility. The model of cyclic evolution of crisis at the enterprise caused by shortcomings of the organizational capital is revealed. It is shown that the organizational capital is a basis for the realization of the human capital, which creates value added. A considerable attention is paid to the experience of the creation and functioning of the organizational capital at the enterprises of the Japanese corporation «Toyota». The Russian economic literature on crisis management quite often considers only the financial aspects of diagnostics, proposing the optimization of cash flows, elimination of excess stocks, transition to the medium-term budgeting and others. However, the deep reasons of crisis need to be found not only in financial streams, but also in the system of the work relationships. The shortcomings in the development of technological, cooperation, economic, moral labor relations and the relations of responsibility directly reflects the shortcomings in the development of the elements of the organizational capital as they «are adjusted» by these elements. In turn, organizational problems affect the product quality leading to the customer attrition and decrease in the enterprise’s financial performance. The lack of financial resources cause the need to save costs (first of all, on personnel, that was brightly shown by the economic crisis of2009) that even more weakens the enterprise and system of labor relations. Finally, the enterprise loses its main resource, which is the personnel with necessary level of knowledge and skills.